Synthesis, Characterization and Antimicrobial Studies of Adducts of Thiotrithiazyl Chloride with Hydrazine and Phenyl Hydrazine - Singh, Anjul; Jadon, S.P.S. (Asian Journal of Chemistry, 2010)
New adducts of thiotrithiazyl chloride with hydrazine and phenyl hydrazine have been synthesized and characterized on the basis of elemental, mass electronic, IR, NMR and ESR spectral studies. The adducts was screened against the gram-ve bacteria, E.coli and S. typhimurium and fungi, C. albicans and C. neoformans. The both hydrazine and phenyl hydrazine adducts are found to be active against the fungi C. albicans and the bacteria E. coli and S. typhi except C. neoformans.